2021
DOI: 10.1136/bmjopen-2021-050571
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality among moderate and severe patients with COVID-19 in India: a secondary analysis of a randomised controlled trial

Abstract: ObjectiveLarge data on the clinical characteristics and outcome of COVID-19 in the Indian population are scarce. We analysed the factors associated with mortality in a cohort of moderately and severely ill patients with COVID-19 enrolled in a randomised trial on convalescent plasma.DesignSecondary analysis of data from a Phase II, Open Label, Randomized Controlled Trial to Assess the Safety and Efficacy of Convalescent Plasma to Limit COVID-19 Associated Complications in Moderate Disease.Setting39 public and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
3
12
1
Order By: Relevance
“…Also, in line with our results, the study by Mammen et al, 27 reported that there was a statistically significant correlation between mortality and invasive ventilation, duration of invasive ventilation, and hospital stay as we found that there was a significantly higher in invasive mechanical ventilation (58% vs 0%) among died cases but noninvasive mechanical ventilation was significantly lower in non-survivors (41% vs 82%), p -value < .001.…”
Section: Discussionsupporting
confidence: 92%
“…Also, in line with our results, the study by Mammen et al, 27 reported that there was a statistically significant correlation between mortality and invasive ventilation, duration of invasive ventilation, and hospital stay as we found that there was a significantly higher in invasive mechanical ventilation (58% vs 0%) among died cases but noninvasive mechanical ventilation was significantly lower in non-survivors (41% vs 82%), p -value < .001.…”
Section: Discussionsupporting
confidence: 92%
“…The studies originated from multiple countries, with 13 of coming from institutions located in the USA [20,21,23,[32][33][34][35]38,42,43,45,48,51]. Nineteen studies included only patients admitted in the ICU [20,22,24,25,27,[30][31][32][35][36][37][38][39][43][44][45][46][47]52], five studies included patients admitted in a COVID-19-dedicated HDU [28,29,33,34,42], eight studies included patients who were admitted in both HDU and ICU [21,23,26,40,41,48,49,51], and one study included Emergency Department patients who were later admitted either in the HDU of ICU [50]. Thirty studies included data about patients who received vs. patients who did not receive vasopressors…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twenty-one out of the 33 included studies provided data on hospital mortality in patients who received vs. patients who did not receive vasopressors, resulting in a total population of 7900 individuals [25,27,[31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48]50,52]. Due to high heterogeneity (I 2 : 94%, PQ<0.001), the random-effects model was implemented.…”
Section: Primary Outcomementioning
confidence: 99%
“…9 Limited studies have evaluated the prognostic biomarkers in developing countries where the burden of Covid-19 is the highest. 10 Only small studies are available from developing countries including India, [11][12][13][14][15][16][17] where the disease led to massive burden and deaths. Measurement of laboratory biomarkers is expensive and not routinely available in most developing countries.…”
Section: Introductionmentioning
confidence: 99%